Creating a Novel Online Digital Badge-Awarding Program in Patient Navigation to Address Healthcare Access. Issue 3 (May 2017) - Rohan, Annie J.; Fullerton, Judith; Escallier, Lori A.; Pati, Susmita
Abstract : A novel, sustainable digital badge-awarding online course was developed to prepare learners with familiarity of patient navigation. Learners offered favorable endorsement of essentially all elements of the program, especially the utility of the Blackboard learning management software program. Quality Matters standards provided a rigorous framework for the challenges of designing, implementing, and evaluating online curricula. Online education is an effective method for meeting the professional development needs of those seeking careers in care coordination/patient navigation.